In/visible war : the culture of war in twenty-first-century America - Lucaites, John Louis; Simons, Jon, 1961- (War Culture Ser., 2017)
"In/Visible War addresses a paradox of twenty-first-century American warfare. The contemporary visual American experience of war is ubiquitous and utterly present in public, popular culture, and yet war is simultaneously invisible or absent; we lack a lived sense that "America" is at war. This paradox of in/visibility concerns the gap between the experiences of war zones and the visual, mediated experience of war in public, popular culture, which absents and renders invisible the former. Large portions of the domestic public experience war only at a distance. For these citizens, war seems abstract, or may even seem to have disappeared altogether due to a relative absence of visual images of casualties. Perhaps even more significantly, wars can be fought without sacrifice by the vast majority of Americans. Yet, the normalization of 21st century war also renders it highly visible. War is made visible through popular, commercial, mediated culture. The spectacle of war occupies the contemporary public sphere in the forms of films, video games, and other media, coming together as MIME, the Military-Industrial-Media-Entertainment Network. This book asks: What is the significance of this simultaneous in/visibility of war? How do militaristic spectacles serve to hide war's costs while simultaneously representing war? How does the in/visibility of war articulate with other structures, processes and practices of social power? Does critical dissent from war depend on other ways of seeing war and rendering it visible?"--Provided by publisher